The effectiveness of aromatherapy, massage and reflexology in people with palliative care needs: A systematic review. (February 2020) - Candy, Bridget; Armstrong, Megan; Flemming, Kate; Kupeli, Nuriye; Stone, Patrick; Vickerstaff, Victoria; Wilkinson, Susie
Background: Aromatherapy, massage and reflexology are widely used in palliative care. Despite this, there are questions about their suitability for inclusion in clinical guidelines. The need to understand their benefits is a public priority, especially in light of funding pressures. Aim: To synthesise current evidence on the effectiveness of aromatherapy, massage and reflexology in people with palliative care needs. Design: A systematic review of randomised controlled trials (PROSPERO CRD42017081409) was undertaken following international standards including Cochrane guidelines. The quality of trials and their pooled evidence were appraised. Primary outcomes on effect were anxiety, pain and quality-of-life. Data sources: Eight citation databases and three trial registries were searched to June 2018. Results: Twenty-two trials, involving 1956 participants were identified. Compared with a control, four evaluated aromatherapy, eight massage and six reflexology. A further four evaluated massage compared with aromatherapy. Trials were at an unclear risk of bias. Many had small samples. Heterogeneity prevented meta-analysis. In comparison with usual care, another therapy or an active control, evidence on the effectiveness of massage and aromatherapy in reducing anxiety, pain and improving quality-of-life was inconclusive. There was some evidence (low quality) that compared to an active control, reflexology reduced pain. Conclusions: This review identified a relatively large number of trials, but with poor and heterogeneous evidence. New clinical recommendations cannot be made based on current evidence. To help provide more definitive trial findings, it may be useful first to understand more about the best way to measure the effectiveness of these therapies in palliative care.